Culture and organizational devices in a family business. job satisfaction and / or personal burnout? (Revista de Investigaciones Universidad del Quindío, 2021)
Objective: the study examined the interweaving of social and psychic determinism of the employee with the ideological framework of the management of a family business from the clinical sociology of work. Material and method: a qualitative-interpretive approach was used, with interviews, review of the organizational manual and clinical analysis of the work. Results: the findings indicate that the members, blood relatives or not, assume responsibilities and replicate behaviors and behaviors within the company, to meet the goals and commitments that the company transmits to them through its power devices. Discussion: the application of organizational instruments implemented from the managerial ideology, such as mission, vision and values, allows satisfying illusions of recognition, omnipotence and opportunities. Conclusions: it is possible to analyze the socio-psychological interrelation of the subject inserted in a business organization, investing it libidinally and bonding with it.
Keywords: Organizational devices; clinical sociology of work; organizational theory; organizational culture; family business